2023
DOI: 10.1002/aur.3055
|View full text |Cite
|
Sign up to set email alerts
|

Auditory language comprehension among children and adolescents with autism spectrum disorder: An ALE meta‐analysis of fMRI studies

Zihui Hua,
Jun Hu,
Huanke Zeng
et al.

Abstract: Difficulties in auditory language comprehension are common among children and adolescents with autism spectrum disorder. However, findings regarding the underlying neural mechanisms remain mixed, and few studies have systematically explored the overall patterns of these findings. Therefore, this study aims to systematically review and meta‐analyze the functional magnetic resonance imaging evidence of neural activation patterns while engaging in auditory language comprehension tasks among children and adolescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 77 publications
0
1
0
Order By: Relevance
“…Functional magnetic resonance imaging (fMRI) has been widely used in clinical studies, as a non-invasive and convenient method, to investigate the neural mechanisms underlying many common mental disorders (e.g., major depressive disorder and schizophrenia) (5)(6)(7). Past fMRI studies have demonstrated that ASD is associated with aberrant brain functions such as significantly decreased/increased functional connectivity (FC) within the visual, frontoparietal (cognition), and language-related subnetworks in the brain (8)(9)(10)(11). These studies have significantly improved our understanding of the complex pathobiology of ASD.…”
Section: Introductionmentioning
confidence: 99%
“…Functional magnetic resonance imaging (fMRI) has been widely used in clinical studies, as a non-invasive and convenient method, to investigate the neural mechanisms underlying many common mental disorders (e.g., major depressive disorder and schizophrenia) (5)(6)(7). Past fMRI studies have demonstrated that ASD is associated with aberrant brain functions such as significantly decreased/increased functional connectivity (FC) within the visual, frontoparietal (cognition), and language-related subnetworks in the brain (8)(9)(10)(11). These studies have significantly improved our understanding of the complex pathobiology of ASD.…”
Section: Introductionmentioning
confidence: 99%